The effect of Ganoderma lucidum spore oil in early skin wound healing: interactions of skin microbiota and inflammation - Jiao, Chunwei (Aging (Albany NY), 2020)
The mushroom Ganoderma lucidum (G. lucidum Leyss. ex Fr.) Karst has been a traditional Chinese medicine for millennia. In this study, we isolated the Ganoderma lucidum spore oil (GLSO) and evaluated the effect of GLSO on skin burn wound healing and the underlying mechanisms. Mice were used to perform skin wound healing assay. Wound analysis was performed by photography, hematoxylin/eosin staining, Masson’s Trichrome staining and immunohistochemical analysis. Microbiota on the wounds were analyzed using the 16s rRNA sequence and quantitative statistics. The lipopolysaccharide (LPS) content was examined in skin wounds and serum using an enzyme-linked immunosorbent assay (ELISA). The expression of Toll-like receptor 4 (TLR4) and the relative levels of inflammatory cytokines were determined by qPCR and immunofluorescence assay. A pseudo-germfree mouse model treated with antibiotics was used to investigate whether GLSO accelerated skin burn wound healing through the skin microbiota. We found that GLSO significantly accelerated the process of skin wound healing and regulated the levels of gram-negative and gram-positive bacteria. Furthermore, GLSO reduced LPS and TLR4, and levels of some other related inflammatory cytokines. The assay with the pseudo-germfree mice model showed that GLSO had a significant acceleration on skin wound healing in comparison with antibiotic treatment. Thus, GLSO downregulated the inflammation by regulating skin microbiota to accelerate skin wound healing. These findings provide a scientific rationale for the potential therapeutic use of GLSO in skin burn injury.